Oxymatrine Liposomes for Intervertebral Disc Treatment: Formulation, in vitro and vivo Assessments - Wang H; Ding Y; Zhang W; Wei K; Pei Y; Zou C; Zhang C; Ding J; Fang H; Tan S (Dove Medical Press, 2020)
Huan Wang, 1,* Yifan Ding, 1,* Wei Zhang, 2 Kang Wei, 1 Yaping Pei, 1 Chenming Zou, 2 Chong Zhang, 2 Jiahui Ding, 2 Huang Fang, 1 Songwei Tan 2 1Department of Orthopaedic Surgery, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China; 2Tongji School of Pharmacy, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huang FangDepartment of Orthopaedic Surgery, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of ChinaEmail fanghuangtjh@hust.edu.cn   Songwei TanTongji School of Pharmacy, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of ChinaEmail tansw@hust.edu.cnPurpose: Intervertebral disc degeneration (IVDD) is the main cause of modern low back pain, leading to high societal economic costs. To find an effective medical treatment for this disease, oxymatrine liposomes (OMT-LIP) were prepared with the pH-gradient method.Materials and Methods: Nucleus pulposus (NP) cells from Sprague–Dawley rats were used for the cell experiments. Kunming mice were used for in vivo imaging. LIP were employed to deliver OMT, and the particle size, ζ-potential, morphology, in vitro stability and in vitro release characteristics were evaluated. The OMT-LIP targeting effect was measured by in vivo imaging. Cell Counting Kit-8 assays were used to detect the cytotoxicity of OMT and OMT-LIP on NP cells. Therapeutic efficacy was measured by Western blot, real-time quantitative polymerase chain reaction, and apoptosis assays. Radiologic analysis was performed to evaluate the therapeutic effects in vivo.Results: Orthogonal test results revealed that the mass ratio of egg yolk phosphatidylcholine to cholesterol was the key factor to effectively trap OMT in LIP. Optimal OMT-LIP showed multivesicular structure with entrapment efficiency of 73.4 ± 4.1%, particle size of 178.1 ± 2.9 nm, and ζ-potential of – 13.30 ± 2.34 mV. OMT-LIP manifested excellent stability in vitro and presented significantly longer sustained release compared to OMT solution in phosphate-buffered saline (pH 7.4). OMT-LIP conspicuously increased OMT accumulation in the degenerative disc, attenuated NP cell apoptosis, reduced the expression of matrix metalloproteinases 3/9 and interleukin-6, and decreased degradation of type II collagen. In in vivo study, X-ray demonstrated that OMT-LIP inhibited IVDD.Conclusion: OMT-LIP may be a useful treatment to alleviate disc inflammation and IVDD.Keywords: intervertebral disc degeneration, liposomes, oxymatrine